Matrix Metalloproteinase-9 as an Important Contributor to the Pathophysiology of Depression - Li, Hongmin; Sheng, Zhaofu; Khan, Suliman; Zhang, Ruiyi; Liu, Yang; Zhang, Yan; Yong, V. Wee; Xue, Mengzhou (Frontiers in Neurology, 2022)
Matrix metalloproteinases (MMPs) are physiologically expressed in the central nervous system in neurons, astrocytes and microglia, and their aberrant elevation contributes to a number of diseases. Amongst the MMP members, MMP-9 has generated considerable attention because of its possible involvement in inflammatory responses, blood-brain barrier permeability, the regulation of perineuronal nets, demyelination, and synaptic long-term potentiation. Emerging evidence indicate an association between MMP-9 and the syndrome of depression. This review provides an updated and comprehensive summary of the probable roles of MMP-9 in depression with an emphasis on the mechanisms and potential of MMP-9 as a biomarker of depression.